Disaster-Responsive Governance dan Kompetensi Guru dalam Membangun Resiliensi Pendidikan pada Pendidikan Islam Pascabencana Banjir - Alfian Sani (Prosiding Seminar Nasional Ilmu Komputer, Sosial Sains, Teknik dan Multi-Disiplin Ilmu, 2026)
Floods are one of the most frequent threats to the continuity of the education system in Indonesia. Their impacts include not only damage to school infrastructure but also reduced quality of educational services, hampered learning processes, and weakened the resilience of educational institutions in facing crises. In the context of Islamic education, these challenges are increasingly complex because teachers are not only tasked with maintaining the continuity of learning but also carry out character development, psychosocial support, and strengthening students’ spiritual values. This study aims to analyze the relationship between Disaster-Responsive Governance and teacher competency in building educational resilience in Islamic educational units after flood disasters. The study used a qualitative approach with a case study design in flood-affected areas in Aceh Tamiang Regency. Data were collected through in-depth interviews, field observations, and analysis of policy documents and reports on educational disaster management. Data analysis was conducted using thematic analysis techniques through data reduction, categorization, interpretation, and conclusion drawing. The research findings indicate that low educational resilience is not solely due to the magnitude of the disaster’s impact, but is also influenced by weak disaster-responsive educational governance, limited coordination between stakeholders, and suboptimal teacher adaptive competencies in dealing with emergency situations. Teachers are required to play a broader role as facilitators of adaptive learning, psychosocial counselors, communication mediators with the community, and reinforcers of Islamic values ​​in the educational recovery process. This research offers a conceptual model that integrates Disaster-Responsive Governance, adaptive teacher competencies, and contextual factors as a foundation for building educational resilience in Islamic educational institutions. This model is expected to serve as the basis for developing more adaptive, inclusive, and sustainable educational policies in disaster-prone areas.